The use of polarography in the initial stages of investigations of mechanisms of organic electrode processes in aqueous solutions - Zuman, Petr (Univerzita Pardubice, 2000)
Initial procedure used in investigation of an organic compound that has not been studied by polarography is described. This is followed by determination of the number of transferred electrons, elucidation of the nature of the process controlling the limiting current, discussion of the role of acid-base equilibria, and proofs of reversibility of the electrode process. Numerous examples demonstrating the use of exoerimental data in elucidation of the sequence of electron and proton transfer in electroorganic processes in protic solvents are given.
Keywords: polarografie; organické sloučeniny; elektrochemické procesy; elektrody; acidobazická rovnováha; protická rozpouštědla